2012
DOI: 10.4028/www.scientific.net/amr.501.294
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting Properties of Calcium Substitution in Barium Site of Porous YBa<sub>2</sub>Cu<sub>3</sub>O<sub>7</sub> Ceramics

Abstract: The influence of calcium substitution at the barium site of porous Y(Ba1-xCax)2Cu3Oδ (x= 0.00, 0.10, 0.20 and 0.30) samples prepared via solid-state reaction method have been investigated. The structure, morphology, critical temperature and critical current were determined by x-ray diffraction (XRD), field-emission scanning electron microscopy (FESEM) and four-point probe method, respectively. Generally, the curves of normalized resistance for all samples displayed normal metallic behavior above Tc onset. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Larger grain size will enhance the grains continuity, lessen the porosity thus enhance the Jc value. Smaller grain size and irregular grain shape induced by Ca substitution in Y146 system will decrease the Jc as compared to that of pure Y123 [8,9].…”
Section: Resultsmentioning
confidence: 99%
“…Larger grain size will enhance the grains continuity, lessen the porosity thus enhance the Jc value. Smaller grain size and irregular grain shape induced by Ca substitution in Y146 system will decrease the Jc as compared to that of pure Y123 [8,9].…”
Section: Resultsmentioning
confidence: 99%
“…The value of J c was increased for samples with low density that has been created by introducing pores. This enhancement of J c is due to the grain alignment of the porous structure [9]. In addition, the increase of J c for porous sample might be due to the good electrical contact within the porous ceramic body rather than one just on the surface as in a dense sample [4].…”
Section: Resultsmentioning
confidence: 99%
“…The strength of super current depends on the proportion of grain boundaries with strong links [17]. This result showed that porous structure samples or low-density samples enhanced the J C due to the slight improvement of grain boundaries [18]. Crystalline sucrose that was used as a filler does not affect the superconductive properties [19].…”
Section: Resultsmentioning
confidence: 99%